Filantropi Biblika sebagai Paradigma Pedagogis Pendidikan Agama Kristen di Tengah Masyarakat Majemuk dan Multikultural - Jerie Refni Boy Maarende; Marojahan Saragi Napitu; Agustinus Pandu Wicaksono (Simpati, 2026)
Indonesian education continues to face serious relational challenges, including declining social empathy, increasing individualism, limited capacity to embrace diversity, and persistent bullying that undermines students' dignity. In this context, Christian Religious Education (CRE) should move beyond the mere transmission of doctrine toward a transformative pedagogical praxis that nurtures compassion, social responsibility, and the courage to transcend identity boundaries for the common good. This qualitative library research examines the narrative of Luke 10:25–37 by analyzing the key terms plēsion, esplanchnisthē, and eleos, and synthesizing these findings with studies on multicultural pedagogy, religious moderation, experiential learning, and Christian education. The findings reveal that the parable of the Good Samaritan is not merely a moral lesson about helping others but a radical critique of religiosity that remains at the level of knowledge without action. Jesus reconstructs the concept of “neighbor” from an identity-based category into an active expression of love that transcends ethnic, social, and religious boundaries. Philosophically, the passage reflects ontological, epistemological, and axiological dimensions that affirm human dignity, love as embodied knowledge, and compassion as the highest moral value. Consequently, Luke 10:25–37 provides a solid biblical foundation for a dialogical, reflective, transformative, and experience-based model of Christian Religious Education. Biblical philanthropy therefore serves as a pedagogical paradigm for developing faithful, compassionate, inclusive, and socially responsible students in a multicultural society.